Coagulation Profile and Outcomes of COVID-19 Patients at Wahidin Sudirohusodo Hospital, Makassar, Indonesia - Jamil, Soraya Wildhani; Ilyas, Muhammad; Ahmad, Nur; Bakri, Syakib; Hardjianti, Tutik; Parewangi, Muhammad Lutfi; Seweng, Arifin (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Coronavirus disease 2019 (COVID-19) is a viral pneumonia infection that spreads rapidly globally (with a number of cases > 15,000,000 worldwide and mortality of ±4%) until it is designated a pandemic by the World Health Organization (WHO). One of the complications of COVID-19 is the incidence of coagulopathy and thromboembolism. The coronavirus, SARS-CoV-2, activates inflammatory and thrombotic processes. Coagulopathy and abnormal coagulation parameters are indicated among the most significant biomarkers of poor prognosis in COVID-19 patients. COVID-19-associated coagulopathy is characterized by a decreased platelet count and the presence of a cytokine storm indicating an extreme hypercoagulable state. This study aims to determine the coagulation profile of moderate-severe patients and outcomes in COVID-19 patients Methods: The study was conducted in a hospital in Makassar: Infection Center RS. Wahidin Sudirohusodo. Medical Record Data for all inpatients who have been diagnosed with COVID-19 through the RT-PCR test taken from January 2021-August 2021.Statistical tests in the form of the Kolmogorov-Smirnov test to assess the Normality of the Data, Chi-Square test, and the calculation of the out ratio (OR) Mann-Whitney test, Independent T-Test. Multivariate analysis was carried out using a Multiple Logistic Regression-Backward Wald Method. The results of the statistical test were significant if the p-value <0.05. Results: The research subjects were 231 patients with confirmed COVID-19. The mean PT, D-Dimer, and Fibrinogen were higher in severe COVID-19 than moderate COVID-19 and had significant results. While PLT did not have significant results against moderate-severe COVID-19. The relationship between groups of coagulation marker variables was found to have a significant relationship with moderate to severe COVID-19. 4. All coagulation markers were significantly related to the outcome (p<0.05). The mean value of each variable was found to be greater in patients with outcomes who died Conclusion: There was an increase in all coagulation markers in moderate to severe COVID-19 except for PLT which was not significant. All coagulation markers are significantly related to outcome